Spore special issue: Family farming: The beginning of a renaissance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2014)
Family farming offers solutions to global challenges. More than 500 million family farms dominate agriculture – ensuring food security, fighting poverty and hunger, providing employment, and enhancing sustainable resource management. Despite challenges, family farms can become prosperous businesses. Forming part of CTA’s support to the UN International Year of Family Farming (IYFF) in 2014, this special issue of Spore addresses topics such as improved production, training and use of technology and local knowledge. It also covers value chains, co-operatives and profitable integration, and the role of the state, so demonstrating how family farms can enjoy a more productive and secure future.